1991
DOI: 10.1002/ddr.430240104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vivo pharmacological profiles of sabeluzole and its enantiomers

Abstract: Sabeluzole, a compound with pronounced cognitive enhancing, antihypoxic, and anticonvulsant properties, is the racemic mixture of the enantiomers R 84 439 (R-configuration) and R 84 440 (S-configuration). Sabeluzole and its separate enantiomers were compared in tests evaluating cognitive enhancing, antihypoxic, anticonvulsant, and secondary activity. Only small differences in potency were observed over species (mice, guinea pigs, and rats), routes of administration (i.p.> s.c., and P.o.), and time intervals (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…A 0 1992 WILEY-LISS, INC. similar improvement of memory was obtained in a pilot study with patients suffering from age-associated memory impairment (Clincke et al, 1992;Tritsmans et al, 1990). Apart from cognitive enhancing activity, sabeluzole has also pronounced antihypoxic and anticonvulsant properties (Wauquier et al, 1986;Werbrouck et al, 1991).…”
Section: Introductionsupporting
confidence: 71%
“…A 0 1992 WILEY-LISS, INC. similar improvement of memory was obtained in a pilot study with patients suffering from age-associated memory impairment (Clincke et al, 1992;Tritsmans et al, 1990). Apart from cognitive enhancing activity, sabeluzole has also pronounced antihypoxic and anticonvulsant properties (Wauquier et al, 1986;Werbrouck et al, 1991).…”
Section: Introductionsupporting
confidence: 71%
“…Non-imidazole structures such as betahistine [17] , phencyclidine [18] , dimaprit [19,20] , clozapine [21] , and sabeluzole [22] which is a benzothiazole derivative, have only weak H 3 antagonist activity. Very recently, Ganellin et al [23] reported a novel series of homologues O and S isosteric tertiary amines of N-ethyl-N-(4-phenylbutyl)amine as potent non-imidazole histamine H 3 receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…The next step was the conversion of the carbamate 2 into the corresponding 2-benzothiazolyl derivative 3. An earlier two-step procedure 12,21,22 was reported to afford 3 by reaction of 2 with isothiocyanatobenzene to give a thiourea intermediate, which in turn underwent oxidative cyclization affording the desired product (overall yield about 71%). Taking inspiration from a procedure reported in the literature for the preparation of various 2-methylamino-and 2-dimethylamino benzocondensed azoles, 23 we explored the possibility of performing the direct coupling of commercially available 2-chlorobenzothiazole with 2.…”
Section: Resultsmentioning
confidence: 98%